Islamic Thought: The Evolution of Science and Technology from Al-Khawarizmi to Abdus Salam - Nana Gustianda (Serambi Madina: Journal of Islamic Studies, 2026)
This study aims to trace the evolution of Islamic thought in science and technology from the classical era to the present day. To prove the continuity between classical and modern thought, this study uses a descriptive qualitative method, which provides an overview of the development of science and technology from the classical era of al-Khawarizmi to the modern era of Abdus Salam through literature review or library research. The results of this study show that there has been continuity from the classical period to the present, with Aljabbar and al-Khawarizmi making significant contributions to science. This study concludes that the development of science and technology has been continuously influenced by the Islamic world, rather than being exclusively the result of the West. However, there are several things that Muslims must pay attention to in order to maintain their intellectual quality.